Effects of internet addiction scores on informational search by undergraduate students - Reed, Phil; Graff, Martin (Telematics and Informatics Reports, 2023)
The study examined the relationship between internet addiction and university students’ use of a network to gain information. Two hundred undergraduate students (aged 18–21 years) were recruited from Science, Social Science, and Arts faculties. They each had 30 min to browse one of two network architectures: a simple hierarchal structure, or a complex relational structure. After the session, they took a test on the content of the network, completed the Internet Addiction Test (IAT), and were asked about their time spent on the internet. There was no effect of university faculty (subject) on any of the results. More pages were revisited using the hierarchical than the relational network structure. However, there were interactions between levels of internet addiction (IAT score) and the type of network. Participants who had lower IAT scores, exposed to hierarchical network, visited a greater proportion of pages, revisited fewer pages, and achieved higher test scores, than lower IAT scorers exposed to the relational network. However, participants with higher IAT scores showed little difference in performance between the networks. There was little impact of IAT score on performance on hierarchical networks, but performance on relational networks improved as IAT scores increased. These data suggest that simple hierarchical networks are better for those with lower internet addiction (as measured by low IAT scores), but there is little difference in network for those with higher internet addiction (higher IAT scores).